ANALISIS REAKSI INVESTOR SEBAGAI DAMPAK COVID-19 PADA SEKTOR PERBANKAN DI INDONESIA - Crescentiano Agung Wicaksono; Rahandhika Ivan Adyaksana (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
This study aims to determine the abnormal return and volume of stock trading transaction due to the Covid-19 pandemic. This research was conducted at banking sector companies listed on the Indonesia Stock Exchange. The research method uses a quantitative approach with the secondary data obtained from Yahoo Finance. This research is an event study of stock prices and trading volume 20 days before and after the announcement of Covid-19 as a global pandemic. Data analysis was performed using Wilcoxon Signed Rank. The results showed there were significant differences in abnormal returns and transaction volume activity before and after the announcement of Covid-19 as a global pandemic. The test results show an overview of the volatility of stock prices and trading volumes that experienced sharp fluctuations during the pandemic. Therefore, investors should also diversify in real assets other than financial asset and consider carefully any investment decisions taken.